Japanese Cultural Values in Doraemon: How Face Threatening Acts Reveal the Implicit Culture of Japan - Theresia Arianti (Mezurashii: Journal of Japanese Studies, 2021)
This study is based on a highly popular Manga across Asia, Doraemon. This study aims to find the Face Threatening Acts contained in Doraemon and how these show Japanese cultural values which contradict American values. Previous studies examining Doraemon mostly do not include Face Threatening Acts in the analysis. Furthermore, they also focus more on the explicit culture contained in Doraemon. These are the gaps fulfilled by this study since it aims to examine the implicit culture of Japan using face Threatening Acts contained in Doraemon.  The result of this study shows that ‘filial piety’ is the Japanese cultural value mostly shown in the story. This study could be used as the base for future studies to examine whether or not Japanese implicit culture in Doraemon was truly the cause of Doraemon’s unpopularity in Japan.